Human regulatory T cells are selectively activated by low‐dose application of the CD28 superagonist TGN1412/TAB08. Issue 4 (1st February 2014) - Tabares, Paula; Berr, Susanne; Römer, Paula S.; Chuvpilo, Sergej; Matskevich, Alexey A.; Tyrsin, Dmitry; Fedotov, Yury; Einsele, Hermann; Tony, Hans‐Peter; Hünig, Thomas
<x xml:space="preserve">Abstract</x> CD28 superagonists (CD28SAs) are potent T‐cell‐activating monoclonal antibodies (mAbs). In contrast to their benign behavior and marked therapeutic efficacy as activators of regulatory T (Treg) cells in preclinical rodent models, a phase I trial of the human CD28SA TGN1412 (now called TAB08) in 2006 resulted in a life‐threatening cytokine release syndrome (CRS). We studied TAB08‐mediated Treg‐cell activation in a recently developed in vitro system of human PBMCs, which also reproduces the CRS experienced by the healthy volunteers. We show that just as in rodents, CD28SAs are potent activators and expanders of Treg cells from healthy donors and rheumatoid arthritis patients, even under effective blockade of pro‐inflammatory cytokine release by a corticosteroid. Moreover, CD28SA titration identifies a dose range where pro‐inflammatory cytokine secretion from conventional T cells is absent while appreciable Treg‐cell activation is maintained. Finally, we report that low‐dose application of TAB08 to healthy volunteers results in dose‐dependent systemic release of the Treg‐cell signature cytokine IL‐10 in the absence of the pro‐inflammatory factors associated with the CRS of the 2006 TGN1412 study. These results demonstrate the potential of appropriately dosed CD28SA and corticosteroid comedication to mobilize human Treg cells for the treatment of autoimmune and inflammatory conditions.